Efficacy and safety of nemolizumab in patients with moderate to severe prurigo nodularis: The OLYMPIA 1 randomized clinical phase 3 trial - Ständer, Sonja; Yosipovitch, Gil; Legat, Franz J.; Reich, Adam; Paul, Carle; Simon, Dagmar; Naldi, Luigi; Metz, Martin; Tsianakas, Athanasios; Pink, Andrew; Fage, Simon; Micali, Giuseppe; et al. (JAMA dermatology, 2024)
Prurigo nodularis (PN) is a chronic and debilitating skin condition, characterized by intense itch with multiple nodular lesions. Nemolizumab demonstrated significant improvements in itch and skin nodules in adults with moderate to severe PN in a previous 16-week phase 3 study (OLYMPIA 2).To assess the efficacy and occurrence of adverse events in adults with moderate to severe PN treated with nemolizumab vs those receiving placebo.OLYMPIA 1 was a multicenter, placebo-controlled, phase 3 randomized clinical trial, conducted from August 2020 to March 2023 at 77 centers across 10 countries in adults with moderate to severe PN (at least 20 nodules and an Investigator’s Global Assessment [IGA] score ≥3) and Peak Pruritus Numerical Rating Scale (PP-NRS) score of at least 7.0; consisted of screening (up to 4 weeks), 24-week treatment, and 8-week follow-up periods.Patients were randomized (2:1) to nemolizumab monotherapy, 30 mg or 60 mg (depending on baseline weight of less than 90 kg vs 90 kg or greater, respectively), or matching placebo administered every 4 weeks for 24 weeks.The primary end points were the proportion of patients with itch response (≥4-point improvement from baseline in weekly average PP-NRS) and IGA success (score of 0/1 [clear/almost clear] and 2-grade or more improvement from baseline) at week 16.Of 286 patients (mean [SD] age, 57.5 [13.0] years; mean [SD] body weight, 85.0 [20.7] kg; 166 [58.0%] female), 190 were randomized to receive nemolizumab, and 96 were randomized to placebo. A significantly greater proportion of patients assigned to nemolizumab vs placebo achieved itch response (111/190 [58.4%] vs 16/96 [16.7%]; Δ, 40.1% [95% CI, 29.4%-50.8%]; P < .001) and IGA success (50/190 [26.3%] vs 7/96 [7.3%]; Δ, 14.6% [95% CI, 6.7%-22.6%]; P = .003) at week 16. At week 24, the proportion of patients with itch response was 58.3% vs 20.4% (Δ, 38.7% [95% CI, 27.5%-49.9%]) in the ad hoc analysis, and IGA success was 58/190 (30.5%) vs 9/96 (9.4%) (Δ, 19.2% [95% CI, 10.3%-28.1%]) in the nemolizumab-treated vs placebo group. During the treatment period, 134 patients (71.7%) receiving nemolizumab vs 62 patients (65.3%) receiving placebo had at least 1 adverse event; most events were of mild to moderate severity.In this randomized clinical trial, nemolizumab monotherapy led to clinically meaningful and statistically significant improvements in core signs and symptoms of PN.ClinicalTrials.gov Identifier: NCT04501666